Ms. Bixby's last day - Anderson, John David, 1975- (Walden Pond Press, an imprint of HarperCollinsPublishers, 2016)
Loving their gifted teacher, three boys are dismayed when the teacher falls ill and leaves for the rest of the school year, a situation that compels them to share their stories while cutting class and journeying across town together on a fateful day.